Synthesis and Electrical Characterization of Zinc Stannate (Zto) Prepared by Hydrothermal Method - Ruiz-Leon, D; Ruiz-Leon, D (Sociedad Chilena de Quimica, 2015)
Zinc Stannate was prepared at 200 °C by hydrothermal method. The X-Ray diffraction data indicate the obtained compound crystallized in the Fd3m space group characteristic of a cubic spinel structure. SEM-EDX and backscattered electrons show and confrm the purity and homogeneity of the fnal sample. The ZTO pressed pellet, sintered at 825 °C, for 1 h, reveals a single, slightly fattened, impedance semicircle and homogeneous electrical microstructure.